Electromagnetic heating for industrial kilning of malt: a feasibility study - Ferrari-John, R.S.; Katrib, Juliano; Zerva, Evgenia; Davies, Nigel; Cook, David J.; Dodds, Chris; Kingman, S.W. (Springer Verlag, 2016)
Industrial malting operations use ~800kWh/t of energy to produce the heat required to kiln malt. Electromagnetic heating technologies are suggested as a way to potentially improve the energy efficiency of the kilning processing. In this work, the potential for using electromagnetic heating to dry malt to commercially acceptable moisture levels, whilst preserving the activity of enzymes critical for downstream brewing processes is investigated. The 2450 MHz bulk dielectric properties of malt at moisture contents consistent with those occurring at different points in the kilning process are evaluated; 12% is shown to be a critical moisture level below which drying becomes more energy intensive. Calculated penetration depths of electromagnetic energy in malt at radio frequency are 100 fold higher than at microwave frequencies, showing a significant advantage for commercial scale batch processing. The moisture contents and alpha and beta amylase activity of malt subjected to RF heating at different temperatures, treatment times and RF energy inputs in the intermediate and bound water drying regions were determined. It is shown for the first time that whilst significantly reduced process times are attainable, significant energy efficiency improvements compared to conventional kilning can only be achieved at higher product temperatures and thus at the expense of enzyme survival. It is suggested that RF heating may be feasible where higher bulk temperatures are not critical for downstream use of the material or when used in hybrid systems.